IMPLEMENTASI SISTEM PELAPORAN SARANA DAN PRASARANA KEGIATAN BELAJAR MENGAJAR BERBASIS ANDROID (STUDI KASUS : INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA) - Yuni Puspita Sari; Rionaldi Ali (Jurnal Informatika, 2019)
Informatics and Business Institute Darmajaya is one of higher education institute that conduct quality standard in service area.  Acknowled gement to the service proven by ISO 9001:2015 certificate issued by International Standard Organization since 2008.  One of standard in our quality standard is concern about the quality of service, and impremented in the form of fascility monitoring in Darmajaya campus.  Facilities and infrastucture particulary classromm and laboratorium which is the main aspect in the learning process between lecturer and student to conduct course interaction.This application designed to build a system to collect complaint report that could help to support course interaction.  Prototype model used in the design of these system.Our reseach has been resulting and application to collect complaint report about facilities and infrastucture than run on android based system.  The application give support to process the report and also complaint system information.  We concluded that our system can be use for real-time monitoring for facilities and infrastucture.   Keywords: Facilities and Infrastructure, Complaint Report Information System, Android Base.